SIFAT ANTAGONIS Trichoderma reesei TERHADAP Colletotrichum sp. SECARA IN VITRO DAN SUMBANGANNYA PADA PEMBELAJARAN BIOLOGI DI SMA - Triana Septiyani; Khoiron Nazip; Endang Dayat (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sriwi, 2023)
ABSTRACTResearch has been conducted on the antagonistic nature of Trichoderma reesei to Colletotrichum sp. in vitro to determine the mechanism of Trichoderma reesei in inhibiting the growth of Colletotrichum sp. This research method is an experiment with descriptive analysis consisting of 3 treatments and 5 repeats. The parameters observed were colony color change and hyphal spread, hyphal shape, hyphal interaction, antagonistic mechanism, and percentage of growth inhibition. The results showed that changes in colony color and spread of hyphae Trichoderma reesei and Colletotrichum sp. has a very obvious difference. Trichoderma reesei has small spherical hyphae, while Colletotrichum sp. produces conidia shaped like crescents. The interaction in treatments 1 and 2 showed the growth of Colletotrichum sp. inhibited because the conidia Trichoderma reesei spread growing on the mycelium of Colletotrichum sp. Meanwhile, treatment 3 showed the entanglement of Trichoderma reesei hyphae to Colletotrichum sp. which causes lysis. The antagonistic mechanisms seen from the observations are mycoparasites, competition, antibiosis, and chitinase enzyme activity. The percentage of inhibition shows that Trichoderma reesei fungus has maximum inhibitory power against Colletotrichum sp. due to the inhibitory power of Trichoderma reesei more than 50%. The results of the study can be used as an alternative example of learning Biology in high school grade X KD 3.6. Apply classification principles to classify fungi based on their characteristics and ways of reproduction through careful and systematic observation, and relate their role in life and the environment. Key Words : Antagonis, Colletotrichum sp., Trichoderma reesei